Respons guru IPA terhadap pelatihan bioteknologi nata de coco pada kegiatan PKM MGMP IPA Kabupaten Bantaeng - Nurhayani H. Muhiddin; Ratnawaty Mamin; Rifda Nur Hikmahwati Arif; Sitti Saenab; Sahribulan Sahribulan (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner of this Community Partnership Program (PKM) was a the MGMP IPA of Bantaeng Regency. The problem with this dedication is that there are still many science teachers who have not mastered Nata de Coco biotechnology. While they as educators in junior high schools must master several applications of biotechnology to manage practicum in Biotechnology learning materials according to the curriculum. Biotechnology training is very appropriate for Science Teachers, so that their insights and skills in practicum management especially on biotechnology materials can be sufficient as an effort to increase the competence of professional teaching staff. The expected output target in this PKM activity is that science teachers have the knowledge and skills in Nata de Coco biotechnology. The results of this activity can be developed into one of the learning tools on Biotechnology material in junior high schools. The method used is: lecture, demonstration, discussion, practice and assistance. The results achieved were the response of science teachers to the process of making Nata de Coco, which on average 85% were in the good and very good categories. The response of science teachers to Nata de Coco biotechnology in learning science in class as much as 98% of teachers answered that Nata de Coco biotechnology can be applied in the classroom and can increase students' interest and science process skills, as much as 100% of teachers answer making Nata de Coco can help students understand the benefits biotechnology in everyday life, and as many as 88% of teachers answer making Nata de Coco according to students' abilities and suitable for application in biotechnology learning.